Sociodemographic Risk Factors and Patterns of Medicolegal Injuries in a Tertiary Care Hospital: A Cross-Sectional Public Health Analysis - Muhammad Arsalan Khan; Mehreen Nasir; Zunaira Amin; Afshan Shahid; Samra Munawar (Journal of University College of Medicine and Dentistry)
Objective: To identify sociodemographic and injury-related risk factors associated with medicolegal cases reported at a tertiary care hospital in Lahore, Pakistan, and to explore their implications for preventive public health strategies.